Isquemia hepática experimental e a ação da l-alanil-glutamina - Araújo Junior, Raimundo José Cunha (2010)
The strategies to prevent the hepatic ischemia/reperfusion injury after hepatic resections or transplantation include intermittent control of blood influx to the liver or the use of a substance that could cause a protective effect or increase of the resistance of the hepatic tissue to ischemia. The present study had the objective to evaluate the effect of the use of the L-Alanil-Glutamina in Ratus novergicus submitted the normothermic hepatic ischemia on liver biochemists and imunohistochemistry, as well as evaluating apoptosis present in this experimental model. 30 male rats, with average weight of 300 grams, divided in three groups of 10 rats: Control group, Ischemia Reperfusion group and Glutamine group. Ischemia Reperfusion group received saline solution 0.9% intra-peritoneal (IP), 2 hours before being submitted to laparotomy, and total ischemia by clampping of portal triad for 30 minutes followed of reperfusion for 60 minutes; The Glutamine group received 0,75mg/Kg IP 2 hours before total ischemia for 30 minutes, followed by reperfusion for 60 minutes. Control group was submitted the peritoneal punction 2 hours before the laparotomy, and only manipulation of the biliary tree, without carrying through any clamping. The procedure was carried through under anesthesia (IP) with a solution of Ketamin chloridate , 80 mg/Kg + xilazin chloridate, 10 mg/Kg. To the end of the period of reperfusion the animals had been relaparotomized and blood collected for evaluation of the levels of ALT and DHL, and hepatic tissue samples for imunohistochemistry study with antibody for Caspase-3. The statistics significance was calculated by ANOVA and the post test of multiple comparison of Tukey, using the software GraphPad Prism, version 5.00. The average and error standard of the dosage of ALT, DHL, and of the index of cells marked with Caspase-3 was respectively for the Ischemia Reperfusion group: 270,6+40,8; 2079,0+262,4 and 66,3+13,5; for the Glutamine group: 127,9+31,17; 1019,0+187,9 and 36,6+12,0; for the Control group: 83,3+5,5; 206,6+16,2 and 21,9+111,4. The preconditioning with intraperitoneal L-alanil-glutamine significantly reduces the values of the biochemists markers, in Ratus novergicus submitted to the hepatic ischemia-reperfusion injury, suggesting hepatic protection.